SAGA Complex Subunits in Candida albicans Differentially Regulate Filamentation, Invasiveness, and Biofilm Formation - Rashid, Saima; Correia-Mesquita, Tuana Oliveira; Godoy, Pablo; Omran, Raha Parvizi; Whiteway, Malcolm (Frontiers in Cellular and Infection Microbiology, 2022)
SAGA (Spt-Ada-Gcn5-acetyltransferase) is a highly conserved, multiprotein co-activator complex that consists of five distinct modules. It has two enzymatic functions, a histone acetyltransferase (HAT) and a deubiquitinase (DUB) and plays a central role in processes such as transcription initiation, elongation, protein stability, and telomere maintenance. We analyzed conditional and null mutants of the SAGA complex module components in the fungal pathogen Candida albicans; Ngg1, (the HAT module); Ubp8, (the DUB module); Tra1, (the recruitment module), Spt7, (the architecture module) and Spt8, (the TBP interaction unit), and assessed their roles in a variety of cellular processes. We observed that spt7Δ/Δ and spt8Δ/Δ strains have a filamentous phenotype, and both are highly invasive in yeast growing conditions as compared to the wild type, while ngg1Δ/Δ and ubp8Δ/Δ are in yeast-locked state and non-invasive in both YPD media and filamentous induced conditions compared to wild type. RNA-sequencing-based transcriptional profiling of SAGA mutants reveals upregulation of hyphal specific genes in spt7Δ/Δ and spt8Δ/Δ strains and downregulation of ergosterol metabolism pathway. As well, spt7Δ/Δ and spt8Δ/Δ confer susceptibility to antifungal drugs, to acidic and alkaline pH, to high temperature, and to osmotic, oxidative, cell wall, and DNA damage stresses, indicating that these proteins are important for genotoxic and cellular stress responses. Despite having similar morphological phenotypes (constitutively filamentous and invasive) spt7 and spt8 mutants displayed variation in nuclear distribution where spt7Δ/Δ cells were frequently binucleate and spt8Δ/Δ cells were consistently mononucleate. We also observed that spt7Δ/Δ and spt8Δ/Δ mutants were quickly engulfed by macrophages compared to ngg1Δ/Δ and ubp8Δ/Δ strains. All these findings suggest that the SAGA complex modules can have contrasting functions where loss of Spt7 or Spt8 enhances filamentation and invasiveness while loss of Ngg1 or Ubp8 blocks these processes.